Solve systems by substitution

y = -2 4x - 3y = 18 Substitute the appropriate expression into theother equation of this system. 4x-3( ) = 18 ( y = -2 4x - 3y = 18 solve the system of equations by substitution method , ) 2x - 3y = -1 x = y + 1 2( ) -3y= -1 Substitute the appropriate expression into theother equation of this system. ( 2x - 3y = -1 x = y + 1 solve the system of equations by substitution method , ) y = 6x - 11 -2x - 3y = -7 -2x-3( )=-7 Substitute the appropriate expression into theother equation of this system. ( y = 6x - 11 -2x - 3y = -7 solve the system of equations by substitution method , ) y = -2x + 20 6x - 5y = 12 6x-5( ) = 12 Substitute the appropriate expression into theother equation of this system. ( y = -2x + 20 6x - 5y = 12 solve the system of equations by substitution method , ) -3( ) - 3y = -15 x = -3y + 1 -3x - 3y = -15 Substitute the appropriate expression into theother equation of this system. ( x = -3y + 1 -3x - 3y = -15 solve the system of equations by substitution method , ) |

Students who took this test also took :

Created with That Quiz —
where a math practice test is always one click away.